Swimming speeds of Mediterranean settlement‐stage fish larvae nuance Hjort's aberrant drift hypothesis. (1st August 2017) - Faillettaz, Robin; Durand, Elysanne; Paris, Claire B.; Koubbi, Philippe; Irisson, Jean‐Olivier
Abstract: Historically, the mortality of early‐life stages of marine fishes was supposed to be mostly caused by poor feeding during a critical period and aberrant drifting away from favorable recruitment areas. While fish larvae may display remarkable swimming abilities, Hjort's aberrant drift hypothesis has rarely been tested. In this study, we measured critical swimming speed ( U crit ) of settlement‐stage larvae of six coastal, warm temperate Mediterranean fish species, for which no data were previously available (Sparidae: Boops boops, Diplodus annularis, Spicara smaris, Spondyliosoma cantharus ; Pomacentridae: Chromis chromis ; Mugilidae sp.). Their swimming speeds were comparable with those of other temperate species, but also with the speeds of tropical species, which are considered as very fast swimmers. Mugilidae were the fastest (29.2 cm s −1 ), followed by Pomacentridae (22.8 cm s −1 ) and Sparidae (11.6 cm s −1 ). Most larvae swam in an inertial regime (Reynolds number > 1000). Those swimming speeds were then implemented in a Lagrangian model of the competency period of these species, set in the same area (the Ligurian Sea) and at the same time (June 2014) as the observations. In this modeling experiment, directional swimming strongly increased the proportion of successful settlers, independent of mesoscale hydrological structures. Fish larvae could settle on the coast from as far as tens of kilometers offshore, in just 4 d. These findings suggest that aberrant drift is unlikely to occur for strong swimming temperate larvae and show that larval behavior should be considered on equal footing with ocean currents when assessing larval fish dispersal.